Acehnese EFL Students and Teacher’s Motivational Teaching Strategy in the Classroom - Yaumil Fadhillah (Jurnal Pendidikan Bahasa dan Sastra, 2022)
This qualitative case study aims to find out the nature of students and teacher’s motivational teaching strategy developed by Dornyei (2001) in teaching English in the classroom. The subject of this research was 1 English teacher in SMP Darul Qur’an Aceh Besar. The data were collected from observation checklist and its note. The findings of this research showed from the 35 motivational teaching strategies developed by Dornyei (2001), there are a total twenty-two motivational strategies applied by teacher during the observation. In the first stage, namely creating the basic motivational condition, there are seven strategies applied, in the second strategies, namely generating initial motivation, there are five strategies, in the third stage, namely maintaining and protecting motivation there are nine strategies, and the last stage, namely the encouraging positive retrospective self-evaluation, there are one strategy applied by teacher. The result displayed those motivational strategies received assorted reactions from students, positive and negative. Thus, these findings can be a reflection for increasing quality, fixing and developing English teaching strategy based on students’ need so that it can help teacher in boosting students’ motivation.